From multiculturalism to interculturalism: failure or improvement - Zanotta Calçada, Luís Antonio (2018)
The multiculturalist movement that emerged at the end of the last century recognized the society as integrated by different cultural groups in search of recognition, having formulated several proposals to foment their demands. In view of the persistence and even the exacerbation of problems related to discrimination, a new approach has been suggested: interculturalism. The present article thus seeks to reflect on this change of vision: has interculturalism been a failure or constitutes a mere improvement of multiculturalism?